The dragons of Paris - Sfar, Joann (Magnetic Press, 2025)
What if dragons invaded Paris during the Belle Époque? Writer Joann Sfar and illustrator Tony Sandoval weave their imaginations into a canvas of adventures, battles, sacrifices, love, and humor. A folkloric, playful, and liberating journey, told in breathtaking epic beauty.